Examining the Impact of GDP on the Nepalese Stock Market: Insights from Co-integration and Granger Causality Tests - Krishna Bahadur Thapa, (Pravaha, 2023)
The stock market reflects the national and international economic health. It promotes investment opportunities and the economic growth of the nation. This study examined the long-run relationship between Gross Domestic Product (GDP) fluctuations and the Nepalese Stock Market Index (NEPSE) employing the econometric models. By using the quantitative analysis of data collected from June 2005 to December 2023, this research applied advanced models such as co-integration to explore long-term equilibrium, vectors auto-regression (VAR) to analyze the short-run impact, and Grangers’ causality tests for identifying cause and effect, and variance decomposition for the quantify the impact. Analyzing the unit root tests revealed that GDP growth rates and stock market indices are integrated at the second difference, leading to the application of the Johansen co-integration test. Results showed no evidence of long-term co-integration between GDP and NEPSE. As a result, a Vector Auto-Regression (VAR) model is employed to assess the short-term dynamics. The VAR analysis indicated that lagged values of NEPSE have a significant positive effect on current NEPSE values. Granger causality tests revealed that GDP has a significant causal impact on NEPSE, but NEPSE does not significantly influence GDP. Variance decomposition analysis further demonstrated that NEPSE’s own past values predominantly drove its oscillations, while GDP had minimal impact on the NEPSE.